2015
DOI: 10.1016/j.ijchp.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of dropout in a controlled clinical trial of psychotherapy for moderate depression

Abstract: A significant number of psychotherapy clients remain untreated, and dropping out is one of the main reasons. Still, the literature around this subject is incoherent. The present study explores potential pre-treatment predictors of dropout in a sample of clients who took part in a clinical trial designed to test the efficacy of narrative therapy for major depressive disorder compared to cognitive-behavioral therapy. Logistic regression analysis showed that: (1) treatment assignment did not predict dropout, (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
1
13
0
3
Order By: Relevance
“…For psychological treatment, other researchers would have to corroborate whether CR is a vulnerability element common to Anxiety and Depressive disorders. Furthermore, in line with the results of Lopes, Gonçalves, Sinai, and Machado (2015) , it would be of interest to study whether CR can predict patients exclusively with depressive disorders quitting therapy compared to those with anxiety and depression comorbidity.…”
Section: Discussionmentioning
confidence: 92%
“…For psychological treatment, other researchers would have to corroborate whether CR is a vulnerability element common to Anxiety and Depressive disorders. Furthermore, in line with the results of Lopes, Gonçalves, Sinai, and Machado (2015) , it would be of interest to study whether CR can predict patients exclusively with depressive disorders quitting therapy compared to those with anxiety and depression comorbidity.…”
Section: Discussionmentioning
confidence: 92%
“…Factors shown to increase an individual's vulnerability for relapse and recurrence include a history of depression, psychiatric illness, the quality of any recovery from a previous episode, is a woman, a history of family depression, and any recent loss ( Judd et al, 2000 , Richards, 2011 , Solomon et al, 2000 , Solomon et al, 2008 ). In addition research has shown how factors such as depressed patients with comorbid anxiety and not taking medication are at risk of dropping out from treatments ( Lopes, Gonçalves, Sinai, & Machado, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Olubukola T Idoko 2014 [89] NR [91] NR No China NR Retrospective research from RCT NR 10 RCTs Q Zhang2014 [92] NR No China NR Theoretical research NA Not applicable YG Li2014 [93] Diabetes No China NR Retrospective research from RCT 51 14 RCTs P Huang 2014 [94] NR Public China NR Theoretical research NA Not applicable YG Li2014 [95] NR No China NR Theoretical research NA Not applicable J Wei2014 [96] NR No China NR Theoretical research NA Not applicable Wenke Zheng2014 [97] NR No China NR Retrospective research from RCT NR Not applicable Lopes R T 2014 [98] Major depressive disorder public Portugal Adults RCT 63 Not applicable S Knippschild2013 [99] Cataract Warner E T2013 [101] Overweight/Hypertension Public USA Adults Implementation research…”
Section: Women Focus Group Interview 102mentioning
confidence: 99%